Hydrostatic pressure effects on the Landé g∥ factor in GaAs–Ga1−xAlxAs quantum heterostructures under applied magnetic fields (2010)
We have performed a theoretical study of the hydrostatic pressure effects on the conduction-electron Landé g∥ factor in GaAs–Ga1−xAlxAs quantum heterostructures (QHs) under the influence of applied magnetic fields. Numerical calculations are performed by using the Ogg–McCombe effective Hamiltonian, which include nonparabolicity and anisotropy effects for the conduction-band electrons. The QHs is assumed to consist of a finite-length cylinder of GaAs surrounded by Ga1−xAlxAs barrier. Theoretical results are given as functions of the radii, lengths, hydrostatic pressure, and applied magnetic fields. We have studied the competition between the geometrical and magnetic confinement versus hydrostatic pressure effects, finding that the geometrical confinement commands the behavior of the g∥ factor. Present theoretical results are in very good agreement with previous experimental and theoretical reports in GaAs–Ga1−xAlxAs heterostructures.